Analisis Pelaksanaan Sistem Tanggap Darurat Bencana Kebakaran pada Karyawan di Rumah Sakit X Tahun 2024: Analysis of the Implementation of the Fire Disaster Emergency Response System for Employees at Hospital X in 2024 - Cahya Arum, Assandra; Sobar Darmadja; Cici Demiyati (MPI Press, 2025)
Introduction: An effective fire emergency response system is a critical element in ensuring safety within hospital environments, where high occupancy, vulnerable patients, and complex infrastructure increase fire-related risks. Hospitals are required to implement comprehensive fire safety management systems to protect employees, patients, visitors, and physical assets. However, gaps in preparedness, particularly related to human resources and procedural awareness, remain a challenge. This study aims to identify and prioritize issues related to fire emergency response readiness, develop alternative improvement strategies, and determine priority actions at Premier Bintaro Hospital. Methods: This study employed a descriptive qualitative design. Data were collected through direct observations, in-depth interviews with key hospital personnel, and document analysis of fire safety policies, training records, and maintenance documentation. The qualitative approach enabled an in-depth understanding of existing fire emergency response practices and institutional preparedness. Results: The findings indicate that several fire safety components at Premier Bintaro Hospital, including employee development initiatives and the availability of active fire protection facilities such as fire extinguishers, fire alarms, and smoke detectors, generally comply with applicable safety standards. Nevertheless, critical gaps were identified, particularly in the consistency of routine fire emergency training, employee awareness of evacuation procedures, and the completeness of maintenance documentation for fire protection systems. Conclusion: This study recommends strengthening routine coaching and training programs, improving staff awareness of fire evacuation procedures, and enhancing documentation and monitoring of fire protection facility maintenance. Optimizing these measures is expected to improve hospital preparedness, minimize potential losses due to fire incidents, and reinforce the implementation of an effective fire safety management system within the hospital environment.